Examining the latent structure of emotional awareness and associations with executive functioning and depression. Issue 4 (19th May 2021) - Eckland, Nathaniel S.; Letkiewicz, Allison M.; Berenbaum, Howard
ABSTRACT: Emotional awareness is comprised of dispositions towards and knowledge about one's emotions. Executive functions (EF) are cognitive processes that organise and guide behaviour towards one's goals. Both emotional awareness and EF play a role in processes such as emotion regulation and are risk factors for the development and maintenance of depression. Although previous research suggests that aspects of emotional awareness are related to EF, methodological and measurement limitations within the available literature make it difficult to clearly understand how they are associated. In this registered report, we examined the extent to which task-based measures of a specific EF process, shifting, are differentially related to unique facets of emotional awareness (i.e. emotional clarity of type, emotional clarity of source, voluntary attention to emotions, and involuntary attention to emotions), and to what extent EF and emotional awareness are related to depression. Using structural equation modelling, we found evidence that emotional clarity of type was associated with greater shifting cost. Shifting was not associated with any other facet of emotional awareness. Depression was linked to lower emotional clarity of type, higher involuntary attention to emotions, but not poorer EF performance. We discuss how emotional awareness and EF may be uniquely related to depression.